A novel ultra-performance liquid chromatography hyphenated with quadrupole time of flight mass spectrometry method for rapid estimation of total toxic retronecine-type of pyrrolizidine alkaloids in herbs without requiring corresponding standards. (1st March 2016) - Zhu, Lin; Ruan, Jian-Qing; Li, Na; Fu, Peter P.; Ye, Yang; Lin, Ge
Highlights: Rapid measurement of hepatotoxic RET-PAs not requiring corresponding standards. Any RET-PA could be used for calibration to estimate total contents of PAs. Comparable to conventional quantitative method that requires the use of standards. Successful application for quantitative estimation of toxic PAs in fifteen potential PA-containing herbs. Suitable for high-throughput quantitative screening PA-containing products. Abstract: Nearly 50% of naturally-occurring pyrrolizidine alkaloids (PAs) are hepatotoxic, and the majority of hepatotoxic PAs are retronecine-type PAs (RET-PAs). However, quantitative measurement of PAs in herbs/foodstuffs is often difficult because most of reference PAs are unavailable. In this study, a rapid, selective, and sensitive UHPLC-QTOF–MS method was developed for the estimation of RET-PAs in herbs without requiring corresponding standards. This method is based on our previously established characteristic and diagnostic mass fragmentation patterns and the use of retrorsine for calibration. The use of a single RET-PA (i.e. retrorsine) for construction of calibration was based on high similarities with no significant differences demonstrated by the calibration curves constructed by peak areas of extract ion chromatograms of fragment ion at m / z 120.0813 or 138.0919 versus concentrations of five representative RET-PAs. The developed method was successfully applied to measure a total content of toxic RET-PAs of diversified structures in fifteen potential PA-containing herbs.